Designing a device to enhance selfconfidence and accuracy of shooting in the basketball (an experimental study) - SABAH JASIM, YASAR; Alwan Hassoon, Tahreer; Ahmed Shakir, Luhaib (International Journal of Psychosocial Rehabilitation, 2020)
Achieving good sporting results in any type of sporting activity has become the distinctive character of our present age, and this did not come out of a vacuum but rather as a result of the use of knowledge and some different sports sciences as well as extensive studies in scientific research, especially in the field of sports training. Basketball is one of the sports that is widely practiced and occupies a good position today, as it has become so beautiful and magnificent that it has made those who practice it have the desire to express their rhythmic performance, as it is the wonderful mixture of many different skills, whether offensive or defensive, that participate to appear in a wonderful painting in which he expresses the players individually and collectively about their abilities in mastering these skills in games, especially when recording points (correction) high skill of accuracy and speed of the player born Wen. Also, the psychological aspect is considered one of the most important and basic aspects in preparing and preparing players for skills in general and correcting in particular. The shooting skill and its various types, especially shooting from afar in basketball, is one of the offensive skills and is the basis of the offensive skill performance, as the entire movements and skills end in the last resort because this skill is the final outcome of the match’s outcome. On the one hand, Youssef Al-Bazi and Mehdi Najm confirm that "Correction is the main goal that must be paid attention to more than other basic skills" (Yusef, 1988) On the other hand, it is a major measure to know the level of players and their ranking in this skill and its various types that are done through scoring points and determining the winning and losing teams as well as their ranking in the league. Therefore, emphasis was placed on the followers of several methods in the field of training. And since the basketball game is one of the games that contain multiple skills as in correction, it is considered the basis of match results, that self-confidence, accuracy and angle of correction are fundamental factor in the results of matches, the widespread use of devices and tools in developing the game of basketball opens wide horizons for coaches and helps them In terms of physical and artistic, and at other times artistic and physical. The importance of the research lies in the importance of the device in developing and enhancing self-confidence and giving it confidence in correcting the fact that this device is designed to develop more accurate and faster correction because the device contains modern technology through iterations that build accurate movement programs based on the internal construction of the optimal model of performance and thus the player His performance has evolved through these two variables that develop the ideal accuracy of the players and therefore the researchers used this device for the purpose of enhancing confidence in the same player and developing the accuracy of correction and thus obtaining better results in matches as the correction occupies a large place among the skills and what should be worked on in order to develop it to achieve The best level.